Analysis of Financing Sources of OMV PETROM S.A. - Cristian Alexandru VASILESCU; Mair AMZA; Raluca Ana VASILESCU; Carol Cristina GOMBOS (Communications of International Proceedings, 2021)
About 160 years ago, Romania began the production and refining of crude oil, being one of the first countries in the world to produce crude oil, becoming one of the largest producers at the beginning of the twentieth century. OMV Petrom is one of the largest companies in Romania that supplies energy from Romania and South-Eastern Europe. It is a value chain of energy from the production of fuels, oil and gas wells to electricity. Large oil companies have seen a decline in sales, as a consequence of the fact that the price of oil has been negative and the demand for petroleum products has fallen due to the reduction or cessation of many activities during the pandemic. The half-yearly report issued by OMV Petrom shows the major impact of the COVID-19 pandemic on the global economy, especially in the first quarter of 2020, when the price of oil reached even negative values.
Keywords: Finance; enterprises; petrol; capital